Understandable electric circuits - Wang, Meizhong, 1955- (Stevenage : Institution of Engineering and Technology, 2010)
This title provides an introduction to the fundamentals of DC/AC circuits. All important concepts, rules and formulas are highlighted after the explanation and are also summarised at the end of each chapter.
Basic concepts of electric circuits -- Basic laws of electric circuits -- Series-parallel resistive circuits -- Methods of DC circuit analysis -- The network theorems -- Capacitors and inductors -- Transient analysis of circuits -- Fundamentals of AC circuits -- Methods of AC circuit analysis -- Mutual inductance and transformers -- Circuits with dependent sources.
Includes bibliographical references and index.
Keywords: Electric circuits